HUBUNGAN KECERDASAN EMOSI DENGAN KEDISIPLINAN ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 1 PEKANBARU - Rahmah Anugrah Putri; Daviq Chairilsyah; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the correlation between emotional intelligence and discipline on children 5-6 years old at Pembina 1 Kindergarten Pekanbaru. The population of this research is 53 students 5-6 years old at Pembina 1 Kindergarten Pekanbaru. Because of the large population, determine the sample is using Random Sampling Technique, that is sample determination technique by taking random. For that set sample of 53 people using Taro Yamane formula. The technique of data analysis is using product moment correlation technique with SPSS for windows version 17 program. Based on the result of the hypothesis test there is a significant positive correlation between emotional intelligence and discipline in children in 5-6 years old at Pembina 1 Kindergarten Pekanbaru. This can be known from the value of the correlation coefficient of rxy =0,599 and significance level 0,000<0,05. The level of correlation between emotional intelligence and discipline included in the medium category with the value of determinant coefficient is equal to KD = r² x 100% = 35,8%, it means that emotional intelligence gives effect of 35,8% to discipline.Key Word: Discipline, Emotional Intelligence